수학·정보 융합교육을 위한 코딩과 연계한 교수학습 자료 개발 연구 - 신기철; Gicheol Shin; 서보억; Boeuk Suh (과학교육연구지, 2019)
이 연구는 수학과 정보교과의 융합교육을 위한 시도로, 최근 강조되고 있는 코딩교육을 수학교육에 접목한 교수학습자료의 개발연구이다. 코딩교육을 위한 수학주제로 전자서명을 선택하였고, 코딩을 위한 프로그램으로는 SageMath이다. 본 연구에서 전자서명의 다양한 방법 중 타원곡선 전자서명 알고리즘에서 이용되는 수학을 조명하고, 이를 소재로 정보와 수학교과의 융합 교수·학습 자료를 코딩기반으로 개발하였다. 최근에 많은 사람들이 관심을 가진 비트코인의 거래에서 실제로 활용되는 타원곡선 전자서명 알고리즘은 수학이 응용되는 실례로서 학생들에게 보여주기 좋은 소재이고, 코딩으로 구현하기에도 최적의 환경을 제공해 주고 있다. 따라서 이를 소재로 한 수업은 수학중심의 융합교육을 실현할 수 있는 구체적인 교수·학습 프로그램을 제공할 것으로 기대된다. 또한 이 연구에서 제시된 교수·학습 프로그램은 수학자, 현장수학교사, 수학교육 전문가의 의견을 종합적으로 고려하여 수정 보완하여 완성함으로써 과학고등학교, 수학동아리, 대학교 ‘정수론’ 강좌 등에서 유의미한 수업으로 구현될 것으로 기대된다. This study, as an attempt to integrate mathematics and information for convergence education, was conducted to develop teaching-learning materials on mathematics education combined with coding education, which has recently been emphasized. We chose the subject of digital signature for coding education, and used SageMath as a coding program. In this study, we overview mathematics used in the elliptic curve digital signature algorithm, one of the many methods for digital signature, and developed the teaching-learning materials on the algorithm for mathematics education integrated with information education based on coding. The elliptic curve digital signature algorithm utilized in transactions of Bitcoin, which many people recently are interested in, is a good example, showing students that mathematics is applied to problem-solving in the real world and provides an optimal environment for implementation by coding. Accordingly, we expect that a class on algorithm will provide a specific teaching-learning program to achieve the goal of integrated mathematics education. By comprehensively considering the opinions of mathematicians, mathematics teachers and mathematics education experts, we expect that the teaching-learning program will be realized as a meaningful class in science high schools, high school’s math clubs, and ‘number theory’ class in colleges.